Development of a decision support system for a transport company. An application for the Revenue Management and non-linear programming - Mendoza-Quispe, José Antonio (2016)
This study develops a planning approach to enable interprovincial land-transport companies to maintain an efficient travel schedule, considering the availability of their medium and long-term resources and the application of revenue management to obtain higher incomes through the use of information technologies. The development of a decision-support system in this sector will allow travel schedule focuses for optimizing the total marginal contribution in the long term, i.e. the difference between incomes and variable costs, as well as an appropriate allocation of resources to the trips, and that the fares established are adequate for the company to reach its goals.